BLOOD DATING BASED ON HAEMOGLOBIN DERIVATIVES (Journal of Forensic Medicine & Toxicology, 2020)
The age determination of bloodstain on a crime scene is significant to determine the exact time since the crime must have taken place. Many techniques have been developed to estimate the age of the bloodstain. In this review paper, various new techniques have been discussed and compared on the basis of convenience, reliability and result accuracy with relation to the data of estimated age v/s actual age on the basis of the haemoglobin components, i.e. Oxyhaemoglobin, Met-haemoglobin and Hemichrome. Five most reliable techniques have been considered for the comparative analysis, i.e. Visible Reflectance Spectroscopy with Chemometric Methods, Hyperspectral Imaging, Reflectance Spectroscopy with Microspectrophotometer and Pre-Processing, Diffused Reflectance Spectroscopy and HPLC. The kinetics related to the degradation of haemoglobin to its derivatives has been discussed. The article includes the error percentage for these techniques with their merits and demerits in their utilization in the field of forensic science.
Keywords: Forensic; Bloodstain; Haemoglobin; Aging; Oxyhaemoglobin; Met-haemoglobin